2013
DOI: 10.1371/journal.pone.0070326
|View full text |Cite
|
Sign up to set email alerts
|

Educational Intervention Increased Referrals to Allopathic Care by Traditional Healers in Three High HIV-Prevalence Rural Districts in Mozambique

Abstract: IntroductionDelayed uptake of clinical services impedes favorable clinical outcomes in Mozambique. Care is delayed among patients who initiate care with traditional healers; patients with conditions like human immunodeficiency virus (HIV) or tuberculosis are rarely referred to the health system in a timely fashion.MethodsWe conducted a pre-post educational intervention with traditional healers, assessing healer referral rates and HIV knowledge in three rural districts in Zambézia Province.ResultsThe median mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 47 publications
0
55
1
1
Order By: Relevance
“…In sub-Saharan Africa countries, referral of HIV-infected pregnant women to facilities has not produced significant increases in PMTCT uptake mainly because of issues with patient transportation to health care facilities and poor provider tracking of referrals. 37,38 Although HBI eliminated a barrier to PMTCT by providing accessible HIV testing sites, it did not eliminate barriers to PMTCT that exist at the health care facility level where ART was provided, as observed in similar studies.…”
Section: Discussionmentioning
confidence: 95%
“…In sub-Saharan Africa countries, referral of HIV-infected pregnant women to facilities has not produced significant increases in PMTCT uptake mainly because of issues with patient transportation to health care facilities and poor provider tracking of referrals. 37,38 Although HBI eliminated a barrier to PMTCT by providing accessible HIV testing sites, it did not eliminate barriers to PMTCT that exist at the health care facility level where ART was provided, as observed in similar studies.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, more effective partnerships between close to community health care workers (community health workers, traditional birth attendants, etc.) and traditional healers must be considered to facilitate referrals and establish a strong system of support for treatment adherence and other HIV care related issues [•15,23,24]. As providers and governments move toward expanded service and scale, retention in care proves to be one of the most important components.…”
Section: The Continuum Of Carementioning
confidence: 99%
“…Once referred to the hospital, patients encounter an additional challenge: a 2012 study in Zambézia found that even when healers referred patients to the health facility, the proportion of patients tested for HIV at first visit was only 3%. 32 Further investigation is needed to determine whether this suggests a lack of respect from allopathic providers for the opinions of healers or reflects a general failure to test symptomatic patients. Following an HIV positive diagnosis, the course of traditional treatments provided is not well understood 33 .…”
Section: Discussionmentioning
confidence: 99%